Determination of Organizational Citizenship Behavior in Outsourcing Employees at PT Kosami Sejahtera Utama - Aulia Dwi Kumala; Puji Wahono; Usep Suhud (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
This study examines the determinants of Organizational Citizenship Behavior (OCB) among outsourcing employees at PT Kosami Sejahtera Utama, an outsourcing company supporting terminal operations at Soekarno-Hatta International Airport. Outsourced workers in Indonesia frequently face job insecurity and low job satisfaction, which negatively affects their willingness to engage in voluntary behaviors beyond formal duties behaviors essential for organizational effectiveness. Preliminary observations at PT Kosami Sejahtera Utama revealed indications of low OCB across multiple dimensions, including reluctance to help coworkers voluntarily and various disciplinary violations. This research employed a quantitative approach with an explanatory design, utilizing a population of 332 employees and a sample of 270 respondents selected through purposive sampling. Data were collected using a structured questionnaire measured on a six-point Likert scale and analyzed using Structural Equation Modeling (SEM) with AMOS version 29. The findings reveal that: (1) job satisfaction has a significant positive effect on OCB (CR=6.848, p<0.05); (2) job satisfaction significantly influences organizational commitment (CR=10.217, p<0.05); (3) work motivation significantly affects organizational commitment (CR=9.389, p<0.05); (4) work motivation significantly influences OCB (CR=6.690, p<0.05); and (5) organizational commitment significantly affects OCB (CR=3.657, p<0.05). These results confirm that enhancing job satisfaction, work motivation, and organizational commitment serves as an effective strategy for fostering employee OCB in outsourcing companies. The research contributes to the application of Social Exchange Theory in non-permanent employment contexts and offers practical implications for improving the sustainable quality of airport operational services through targeted human resource management policies.